A morte de crianças Xavante no período da desintrusão da Terra Indígena Marãiwatsédé - Pena, Angela Campbell (2017)
The Xavante are an indigenous people of Brazil who have become known for resisting the invasion of their lands in the east of Mato Grosso and for constantly suffering from the environmental degradation and fragility of the health services offered to them, which ends up having consequences for the state of health of children. This study was carried out in the Marãiwatsédé indigenous land and it was proposed to analyze the deaths of Xavante children under the age of five and stillbirths in the period of disinfection, which corresponds to the years of 2012 and 2013. During this period, Marãiwatsédé indigenous land was the scene of intense political and A territorial dispute that culminated in a police action to de-intrude squatters and landowners illegally residing in indigenous land. The study made use of the qualitative research in health to the extent that it analyzed the meanings attributed by the indigenous to the deaths of the children and the socioenvironmental and health assistance context in which the deaths occur. The techniques of observation and semi-structured interview with family members of the children were also used. The Death Investigation Record - Domiciliary Interview of the Ministry of Health was also applied. Data analysis was carried out in the light of the interpretation of meanings and the dialogue between Hermeneutics and dialectics, proposed by Minayo. The results indicate that the socioenvironmental context in which the deaths occurred was environmental degradation, food scarcity, population surplus and low water quality, associated with a climate of intense hostility and fragile relationships between the indigenous people and the residents of the surrounding cities. The social impact of deaths on the community. At the time of death, the families showed the use of an eclectic health system that combined healing activities related to the informal sector and the professional health sector, more specifically the biomedical model. In addition, the Indians used a syncretic explanatory model in the definitions of causality of deaths, in that they reconciled elements originating from different models to assign meaning to them. The main meanings attributed to the deaths occurring during the period of disinfection were related to 1) territorial conflict and environment; 2) spirituality and inevitability of death; And 3) medical procedures. Given this, it is evident the importance of analyzing infant deaths beyond the numerical senses, in order to make comprehensible the meaning of sickness and death of those who experienced the deaths in their daily lives, and through intercultural dialogue, produce answers for the planning of actions more appropriate to the indigenous context, either for monitoring children and families or for the humanization of indigenous health care.